Evaluation of an Efficient Modulus in the Biopolymer String Tension - Pata, Vladimir; Suba, Oldrich; Sykorova, Libuse; Kubisova, Milena; Hylova, Lenka; Cernekova, Martina (Manufacturing Technology Journal, 2018)
Application of biopolymer materials is currently a rising trend. However, many problems are often encountered when evaluating and describing their mechanical properties. The present article will describe a procedure for finding a so-called effective modulus of elasticity of a biopolymer material having the shape of a thin string with a diameter of about 100 μm.Subsequently, there are not only problems in the actual evaluation of the tensile test (which will be demonstrated by the assembled 3D model), but also when the sample is sampled, which is decisive for finding an efficient module. The article will deal with the methodology of sample squeezing into the specially developed product, the determination of an elastic modulus from the tensile test and the behaviour of the sample when the strength limit is exceeded, which will be captured and subsequently evaluated by the high-speed camera system.
Keywords: biopolymer fibre; keratin; statistical evaluation; tensile strength